UJI FAKTOR-FAKTOR PEMBEDA KEBIJAKAN DIVIDEN: ANALISIS DISKRIMINAN - Fitri Ismiyanti; Putu Anom Mahadwartha (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2005)
This research tested variables (firm specific and beta) that affected dividend policy in Indonesian firms. Samples are listed firm in Jakarta Stock Exchange (JSX) especially manufacture industry. This research uses discriminant analysis with several tests for data and results to maintain the robustness of the analysis. The results indicate that debt, investment opportunity sets and return on assets are significant in affecting dividend policy. Meanwhile beta fails to discriminate between firms that pay dividend and not pay dividend. The firm specific variables could discriminate between firms that pay dividend and not pay dividend. The results also show that management is more concerned about firm specific variables in dividend policy and less concerned, about systematic risk (beta).